The Moralization of Cigarette Smoking in the United States - Rozin, Paul; Singh, Leher (Journal of Consumer Psychology, 1999)
Moralization refers to the conversion of a preference into a value, within a culture and in individual lives. It is hypothesized that values, because of associated moral meanings, are more likely to produce internalization than instrumental concerns such as health risks. Specifically, it is predicted that liking for and disgust toward a substance or activity will be more extreme if the substance or activity is treated as a value (is moralized). These ideas are tested by attitudes to cigarette smoking, an activity which is undergoing moralization in the United States. Results from questionnaires completed by 715 American participants of 3 generations (college students, their parents, and grandparents) support this hypothesis. Beliefs that smoking is immoral correlate more highly with disgust at and liking for smoking than do beliefs about the health effects of cigarettes. These relations hold across all 3 generations. Retrospective data from the parents and grandparents document decreased liking and increasing health and moral concerns and disgust over the last 20 or 40 years. On the other hand, the history of smoking and living in a society that did not disapprove of smoking seems to have left no residual effects in contemporary judgments of grandparents or parents; their current negative attitudes to smoking are about the same as those of their grandchildren and children. There is weak evidence suggesting that moral attitudes to cigarettes are transmitted more from parent to child than are health beliefs or preferences.